Use of nanotechnology In the Development of Organic Fertilizers and Pesticides - Juan Anderson (GoAcademica Research & Publishing, 2022)
It cannot be denied that the development of technology and its use is closely related to the increase in the competitiveness of a country's industry. Greater knowledge and mastery of new technologies is needed to win competition in the age of global trade by both government and industry. An example of technology that is being discussed is nanotechnology. The use of nanotechnology is well known, including in the fields of health, cosmetics and agriculture. Basically, the principle of nanotechnology discovery is to maximize crop yield or production by minimizing the use of fertilizers, pesticides, and other necessities by monitoring soil conditions, such as roots, and applying them directly to the target so nothing goes to waste. For pesticides, if this is applied, you will be able to minimize the use of pesticides on plants because only the target insects are affected. The use of nanotechnology in fertilizers will allow the release of the nutrients contained in the fertilizer to be controlled. Therefore, only the nutrients that will actually be taken up by the plants are released, so there is no loss of nutrients, no undesirable targets such as soil, water, and microorganisms. In nanofertilizers, the nutrients can be in the form of encapsulation of nanomaterials, covered by a thin protective layer or released in the form of an emulsion from nanoparticles.